FRAME SURVEY OF FISHERIES RESOURCES OF OTAMIRI RIVER: MORPHOECOLOGICAL STUDIES OF FISH SPECIES AND IMPLICATION FOR FISHERIES DEVELOPMENT IN IMO STATE - ONWUKA, C. N; EBOCHUO, V.C; IGBOACHU, L. O. (Nigerian Journal of Fisheries, 2019)
The study explained morpho-ecological adaptation of fish species sampled in Otamiri River, Imo state, Nigeria between May and December, 2017 and February to April, 2018. The indices employed were morphometric, gut and stomach content analysis, condition factor and length-weight relationship. The mean length ranged between 10.40 and 62.45 cm (Tilapia mariae and Malapterurus electricus respectively). The mean weight ranged between 70.50 and 207.55 cm (Tilapia dageti and Phractolaemus ansorgei respectively). Stomach content was analyzed using numerical methods. The fish fed mainly on higher plant materials (20%), fish remain (24%), palm-kernel shaft (22%) and detritus (34%), exhibiting omnivorosity. The fishes have a well-developed gut system. Their relative gut index ranged between 1.20 and 1.30 which supported omnivorous feeding habit. The fishes exhibited an allometric growth pattern, a pattern which supports easier movement in water. With favorable environmental conditions, availability of food and nutrient, the fishes display sustainable fishery production. Strategic management practices should be put in place to avoid over fishing and depletion of the fish stock by the indigenous inhabitants.